Why psychologists do not want to work with older adults – and why they should. . . (22nd October 2014) - Bryant, Christina; Koder, Deborah
Abstract : It is well-documented that the population of much of the developed world is aging. On the one hand, this represents a success story in terms of reducing deaths from infectious and a number of systemic diseases, most notably cardiovascular disease. On the other hand, it also presents a challenge to provide adequate health services to a population with rapidly increasing longevity, as well as an opportunity to develop policies that can assist in promoting good physical and mental health. A number of authors have asked whether we are ready to meet the challenges of an aging population (Doyle et al., 2009; Connolly, 2012). Over the years, prominent psychologists have suggested that clinical psychology could play a greater role in the provision of services for older adults, and lamented the apparent lack of enthusiasm on the part of psychologists to work with this group (e.g. Karel et al., 2012). In this paper, we examine a range of questions pertinent to this theme: where are the psychologists in the provision of mental health services to older adults? What contribution can psychologists make to improve the mental health of this growing sector of the population? How can we encourage more psychologists to specialize in working with older adults?